A Comparison Between The Pharmacokinetics Of Gentamicin And Its Mixture With Calcium In Rabbits - Al-Ubaydi, Murouj Abdul-Sattar; Abbass, Duraid Abdulhadi (The Iraqi Journal of Veterinary Medicine, 2004)
Pharamcokinetic studies were performed for gentamicin sulphate at single dose of 5 mg/kg compared with formullae of same dose of gentamicin with calcium gluconate at a dose of 7.5 mg/kg injected i.v. and i.m. to four groups of 5 rabbits. The results of i.v. injection showed elimination of first order two compartment model with lower plasma gentamicin concentration, lower inhibition bacterial period and increase of gentamicin clearance in mixture group may be due to its competition with calcium for albumin which increase the free drug available for excretion and distribution while after i.m. injection absorption of gentamicin from formullae was lower but its plasma elimination (B) was slower with nearly same inhibition bacterial period as in gentamicin dosed group. These results explain kinetically why calcium lower gentamicin toxic side effect after i.m. and i.v. injection.